2015
DOI: 10.1093/jpepsy/jsu113
|View full text |Cite
|
Sign up to set email alerts
|

Family Density and SES Related to Diabetes Management and Glycemic Control in Adolescents With Type 1 Diabetes

Abstract: Beyond SES, FD plays a significant role in adherence and glycemic control via diabetes-related conflict. In contrast, the effects of single-parent status were indistinguishable from those of SES. FD provides distinct information related to adolescent glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 43 publications
6
27
2
Order By: Relevance
“…21 A collaborative parent-child relationship with shared responsibilities for diabetes management is associated not only with better regimen adherence but also with improved emotional functioning. 69,77,78 Socio-demographic family factors such as singleparent households or higher family density (more youth per adults in the household), [78][79][80][81][82] lower family income, and racial/ethnic minority status 78,[81][82][83][84][85][86][87] are associated with less optimal parental involvement in diabetes management and greater risk for poor control of diabetes.…”
Section: Family Functioning and Social Supportmentioning
confidence: 99%
“…21 A collaborative parent-child relationship with shared responsibilities for diabetes management is associated not only with better regimen adherence but also with improved emotional functioning. 69,77,78 Socio-demographic family factors such as singleparent households or higher family density (more youth per adults in the household), [78][79][80][81][82] lower family income, and racial/ethnic minority status 78,[81][82][83][84][85][86][87] are associated with less optimal parental involvement in diabetes management and greater risk for poor control of diabetes.…”
Section: Family Functioning and Social Supportmentioning
confidence: 99%
“…For example, youth in homes with a larger ratio of children to parents have higher diabetes‐related conflict and those with single parents have higher youth behavior problems, family conflict, parenting stress, and less parent involvement in diabetes management . The relationship between single‐parent family structure and emotional burden may be confounded by low socioeconomic status (SES), which is associated with higher parenting stress, diabetes‐related family conflict, and youth depressive symptoms . Diabetes‐related burdens among low SES families are related to greater exposure to stressors and adversity, as well as less access to tangible (eg, insurance coverage) and psychosocial resources (eg, self‐esteem, optimism, and social support) .…”
Section: Emotional Burdens Of Youth With T1dmentioning
confidence: 99%
“…24,25 Some youth and families are more vulnerable to diabetes-related emotional burdens than others. For example, youth in homes with a larger ratio of children to parents have higher diabetes-related conflict 26 and those with single parents have higher youth behavior problems, family conflict, parenting stress, and less parent involvement in diabetes management. 27,28 The relationship between single-parent family structure and emotional burden may be confounded by low socioeconomic status (SES), 28 which is associated with higher parenting stress, diabetes-related family conflict, and youth depressive symptoms.…”
Section: Emotional Burdens Of Youth With T1dmentioning
confidence: 99%
“…Caccavale et al [23] studied whether family density, using a youth:adult ratio, was a better way to assess family risk status when compared with other SES markers. The authors found that lower family density was associated with better glycemic control via less conflict and greater adherence and argued that family density provides additional information beyond routine SES analysis.…”
Section: Key Pointsmentioning
confidence: 99%